Rosacea pathogenesis and therapeutics: current treatments and a look at future targets - Fisher, Garrett W.; Travers, Jeffrey B.; Rohan, Craig A. (Frontiers in Medicine, 2023)
Rosacea is a chronic inflammatory skin condition associated with a significant health and economic burden from costs and loss of productivity due to seeking medical treatment. The disease encompasses multiple phenotypic manifestations involving a complex and multi-variate pathogenesis. Although the pathophysiology of rosacea is not completely understood, ongoing research is continually elucidating its mechanisms. In this review, current concepts of rosacea pathogenesis will be addressed which involve skin barrier and permeability dysfunction, the innate and adaptive immune systems, and the neurovascular system. More specifically, the cathelicidin pathway, transient potential receptor channels, mast cells, and the NLRP3 inflammasome pathway are various targets of current pharmacologic regimens. Future therapies may seek different mechanisms to act on current treatment targets, like the potential use of JAK/STAT inhibitors in ameliorating skin barrier dysfunction or TLR antagonists in alleviating cathelicidin mediated inflammation. Other potential treatments aim for entirely different molecular targets such as microvesicle particle mediated local and systemic inflammation. Ultimately rosacea is associated with a significant health and economic burden which warrants deeper research into its pathogenesis and with resultant new treatment discovery.